"Why Would I Talk To Them About Sex?": Exploring Patient-Provider Communication Among Black Women Experiencing Sexual Pain. (August 2022) - Thorpe, Shemeka; Iyiewuare, Praise; Ware, Samuella; Malone, Natalie; Jester, Jasmine K.; Dogan, Jardin N.; Hargons, Candice N.
Ineffective patient-provider communication poses a potential health risk to Black women if medical providers are not addressing their needs or concerns. Additionally, less than half of OBGYNs report asking their patients about sexual difficulties, which limits women's opportunities to disclose their experiences of sexual pain. The purpose of this qualitative study is to explore Black women's experiences of patient-provider communication about sexual pain (reoccurring unwanted genital pain). Specifically, we aimed to describe the pathway from sexual pain disclosure to treatment among N = 25 premenopausal Black women living in the southern United States who were experiencing sexual pain. Using constructivist grounded theory, open-ended responses to six interview questions related to healthcare experiences, treatment, and patient-provider communication were qualitatively analyzed and categorized to form a conceptual framework of patient-provider communication about sexual pain. Five key categories emerged related to Black women's experiences with their medical providers regarding sexual pain: (1) provider preferences, (2) healthcare experiences, (3) reasons for non-disclosure, (4) provider responses to sexual pain, and (5) treatment for sexual pain. Useful strategies to improve patient-provider communication are presented for both patients and providers.